IMPLEMENTATION PROGRAM FOR COMPLETE SYSTEMIC LAND REGISTRATION (PTSL) FOR ACCELERATION OF LAND REGISTRATION AT MAKASSAR LAND OFFICE - Aslinda, Andi; Asyifa, Nur; Nur, Andi Cudai (Universitas Negeri Makassar, 2024)
This study aims to find out the Implementation of the Complete Systematic Land Registration Program (PTSL) in the context of Accelerating Land Registration at the Makassar City Land Office as well as the supporting and inhibiting factors for the implementation of the Complete Systematic Land Registration Program (PTSL) at the Makassar City Land Office. This research uses a qualitative approach. Data collection was carried out through observation, interview, and documentation techniques. The data analysis technique used in this study is interactive data analysis through stages: data condensation, data presentation, and conclusion testing.The results of this study show that the Implementation of the Complete Systematic Land Registration Program (PTSL) at the Makassar City Land Office has been running well, although there are still some shortcomings in its implementation. This is seen from the standards and objectives of the policy, the characteristics of the implementing bodies/agencies, communication between organizations, the attitude of the implementers in the implementation of PTSL has been running well, but there are still shortcomings in policy sources and the economic, social, and political environment. The supporting factors in the implementation of the PTSL program are the existence of a clear legal basis, good communication between organizations, and support from the community. Factors that hinder the implementation of the Complete Systematic Land Registration (PTSL) program at the Makassar City Land Office include the lack of human resources, the existence of land in the dispute stage, the delay of the community in collecting administrative requirements, and the existence of land plots whose owners are unknown.